Psychology for the Other : Levinas, Ethics and the Practice of Psychology - Williams, Richard N., 1950-; Gantt, Edwin E., 1965- (Book collections on Project MUSE., 2002)
"In ten original essays by distinguished scholars - some philosophers, some clinicians, and some academic psychologists - the potential and the experiential impact of Levinas's work in the understanding of our fundamental human nature and the practice of psychotherapy are explored. Ultimately, the intention is to create a new discipline of psychology: namely, a "science of the ethical.""--Jacket